2019
DOI: 10.1097/sla.0000000000003271
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on the Outcome in Female Groin Hernia Repair

Abstract: Objective: Based on an analysis of data from the Herniamed Registry, this study aims to identify all factors influencing the outcome in female groin hernia repair. Background: In a systematic review and meta-analysis of observational studies, female sex was found to be a significant risk factor for recurrence. In the guidelines, the totally extraperitoneal patch plasty (TEP) and transabdominal preperitoneal patch plasty (TAPP) laparo-endoscopic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
0
37
1
2
Order By: Relevance
“…Recurrences after inguinal hernia repairs can occur even up to 50 years later [2]. In recent administrative data and registry analyses it was revealed that the proportion of recurrent repairs in the total collective of inguinal hernia repairs among men was 11.3-14.3% [3][4][5][6][7] and in women 7.0-7.4% [4,8]. By contrast, in systematic reviews and meta-analyses the recurrence rates were still far lower (1.2-3%) than those cited above since the included studies had a maximum follow-up time of 6 years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrences after inguinal hernia repairs can occur even up to 50 years later [2]. In recent administrative data and registry analyses it was revealed that the proportion of recurrent repairs in the total collective of inguinal hernia repairs among men was 11.3-14.3% [3][4][5][6][7] and in women 7.0-7.4% [4,8]. By contrast, in systematic reviews and meta-analyses the recurrence rates were still far lower (1.2-3%) than those cited above since the included studies had a maximum follow-up time of 6 years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The rates of second recurrences after recurrent inguinal hernia repair are reported in registry data and case series to be as high as 8.8% [12,13]. In meta-analyses comparing open with laparo-endoscopic repair of first inguinal hernia recurrences the rates of second recurrences were between 2.9% and 9.2% [14][15][16][17], depending on the follow-up time.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic pain rate given in the international guidelines is 0.5-6.0% [1]. The surgical technique, gender, and size of the hernia defect have a decisive impact on the rate of chronic pain requiring treatment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines recommend a laparo-endoscopic technique for repair of femoral hernia in women because of its superior diagnostic and therapeutic value [7]. In systematic reviews and registry analyses, women have been found to be at increased risk for developing chronic pain following repair [36,37]. As such, groin hernia repair in women has more caveats and places an added 'stringent' demand on the surgeon [37].…”
Section: Groin Hernia In Womenmentioning
confidence: 99%
“…In systematic reviews and registry analyses, women have been found to be at increased risk for developing chronic pain following repair [36,37]. As such, groin hernia repair in women has more caveats and places an added 'stringent' demand on the surgeon [37].…”
Section: Groin Hernia In Womenmentioning
confidence: 99%